Educação médica contínua: um apelo e um desafio. - F Sampayo (Acta Médica Portuguesa, 1990)
Professional responsibility of physicians requires continuous Medical Education. The Accrediation Council for Continuing Medical Education has developed in the U.S.A. a perfect program based on the Essentials and guidelines for accreditation. It is urgent to create a national trusty and dynamic structure to make possible the organization and coordination of CME and respective evaluation.